Combined Phacoemulsification and Goniosynechialysis under an Endoscope for Chronic Primary Angle-Closure Glaucoma. (8th February 2018) - Nie, Li; Pan, Weihua; Fang, Aiwu; Li, Zhangliang; Qian, Zhenbin; Fu, Lin; Chan, Yau Kei
Abstract : Purpose . To investigate the clinical efficacy and safety of combined phacoemulsification with goniosynechialysis (GSL) under an ophthalmic endoscope for chronic primary angle-closure glaucoma and coexisting cataract. Methods . This is a retrospective study. The intraocular pressure (IOP), best-corrected visual acuity (BCVA), and number of glaucoma medications at baseline and each postoperative follow-up visit were recorded. Other measurements included supraciliochoroidal fluid measured by anterior segment optical coherence tomography, corneal endothelial cell density (ECD), and peripheral anterior synechia (PAS). All patients were followed for more than a year. Results . Thirty-eight eyes of 31 patients were included. The mean follow-up duration was 16.3 ± 3.9 months. The IOP decreased from 22.2 ± 9.3 mmHg at baseline to 15.4 ± 4.2 mmHg at the last follow-up (P < 0.001 ). The mean number of glaucoma medications (0.1 ± 0.6) at the last follow-up was significantly lower than the preoperative number (2.3 ± 1.1) (P < 0.001 ). All patients achieved improved or stable visual acuity after surgery. All patients achieved a complete opened angle after GSL. The postoperative complications included hyphema (7.9%), exudation (5.3%), transiently elevated IOP (55.3%), and supraciliochoroidal fluid (40%). Conclusions . Combined phacoemulsification and GSL under an endoscope can completely reopen PAS and is an effective and safe method for patients with chronic primary angle-closure glaucoma and coexisting cataract.